2016
DOI: 10.1111/wre.12228
|View full text |Cite
|
Sign up to set email alerts
|

An approach to investigate the costs of herbicide‐resistant Alopecurus myosuroides

Abstract: Herbicide resistance in Alopecurus myosuroides causes severe problems in Western European cropping systems. Costs of herbicide resistance were investigated in this study by analysing variable production costs and sales revenues. Three farms were selected for this study, with winter wheat as the dominating crop in all farms. Resistance in A. myosuroides populations was verified at all locations. Four farming approaches were simulated over a period of 20 years: (i) continuing the actual cropping system without i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 14 publications
1
21
0
1
Order By: Relevance
“…Weed‐control decisions are heavily influenced by economics and utilize systems that provide the greatest measurable, near‐term economic return. In many cases, proactive resistance management comes at a short‐term cost, even though it may enhance long‐term profits …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Weed‐control decisions are heavily influenced by economics and utilize systems that provide the greatest measurable, near‐term economic return. In many cases, proactive resistance management comes at a short‐term cost, even though it may enhance long‐term profits …”
Section: Discussionmentioning
confidence: 99%
“…Some simulations have indicated that, if left unchecked, resistant A. myosuroides may eliminate profitability for some European farmers. 69 The same study indicates that a proactive approach that utilizes a greater diversity of crops, tillage and herbicides may reduce net profitability by 4-24% compared with an intensive cropping system without resistance, but in the long term will be more profitable compared with resistance development. 70 The consequence of evolution of resistance to ACCase and ALS inhibitors in grass species in small grain crops has been an increase in the adoption of pre-emergence herbicides, along with greater use of cultural practices such as occasional inversion tillage and use of false seedbeds, in order to reduce resistance selection pressure and eventually exhaust the seedbank.…”
Section: Herbicide Resistance Managementmentioning
confidence: 97%
See 3 more Smart Citations